Yeast membrane engineering to improve acetic acid tolerance for lignocellulose conversion. - Trivellin, Cecilia (My University, 2019)
Global issues such as climate change, exploitation and waste of resources raise the need for solutions for a more sustainable future. Fossil based chemicals, fuels and energy should be replaced by more sustainable alternatives. Lignocellulose biomass is one of the most abundant raw material on earth, which make it easy to use it for such purposes. However, research involved in transforming this resource into desired products still has issues linked to achieving high yields and productivity. One of those problems is the presence of inhibitory compounds produced during the lignocellulosic biomass pre-treatments, which contribute to reduce the fermentation performances. Inhibitors such acetic acid can, in fact, penetrate inside of yeast cells and alter their metabolism. Studies in this field have shown that the yeast membrane composition and especially its sphingolipids content could be a key point to overcome the acid stress. The specific aim of this thesis was to investigate the role of the different genes involved in the sphingolipid’s biosynthetic pathway in Zygosaccharomyces bailii. This study was conducted to better understand how to engineer the Saccharomyces cerevisiae cell membrane to minimize acetic acid intake. Gene expression analysis showed that genes involved in the biosynthesis of sphingolipids (NVJ2, SAC1, AUR1, LRO1, DGA1, KEI1) are overexpressed while the cells are exposed to acetic acid. This suggested that in the analysed conditions the sphingolipids pathway is highly active. From this study it was possible to select four relevant genes: NVJ2, SAC1, AUR1 and KEI1 which have been subsequently overexpressed in Saccharomyces cerevisiae to observe how the modified strains would react when exposed to acetic acid.
Keywords: Lignocellulose, Biomass, Acetic acid, Pre-treatments, Gene expression analysis